Atraumatic Restorative Treatment in Pediatric Dentistry (REMUNOM, 2023)
Atraumatic Restorative Treatment (ART) is a minimally invasive technique, viable for care aimed at children, due to several operational criteria such as, for example, the non-use of motors. This article aims to explain the advantages, indications and stages of Atraumatic Restorative Treatment in pediatric dentistry. The methodology used was analysis and selection of articles and journals published in recognized databases, such as “Scielo”, “PuMed”, “Google Scholar”, “RevOdonto”, among others. ART is a technique with broad social impact, which reduces the possibility of endodontics and extractions, and therefore chair time, and can be easily applied in offices and environments without equipment. Its limitations lie in the size and retention of the oral cavity, the quality of the restorative material and, mainly, the low acceptance of the technique by professionals and the community.